Implementing Sustainable Data Collection for a Cardiac Outcomes Registry in an Australian Public Hospital - Cox, N.; Brennan, A.; Dinh, D.; Brien, R.; Cowie, K.; Stub, D.; Reid, Christopher; Lefkovits, J. (Elsevier, 2017)
Background: Clinical outcome registries are an increasingly vital component of ensuring quality and safety of patient care. However, Australian hospitals rarely have additional resources or the capacity to fund the additional staff time to complete the task of data collection and entry. At the same time, registry funding models do not support staff for the collection of data at the site but are directed towards the central registry tasks of data reporting, managing and quality monitoring. The sustainability of a registry is contingent on building efficiencies into data management and collection. Methods: We describe the methods used in a large Victorian public hospital to develop a sustainable data collection system for the Victorian Cardiac Outcomes Registry (VCOR), using existing staff and resources common to many public hospitals. We describe the features of the registry and the hospital specific strategies that allowed us to do this as part of our routine business of providing good quality cardiac care. Results: All clinical staff involved in patient care were given some data collection task with the entry of these data embedded into the staff's daily workflow. A senior cardiology registrar was empowered to allocate data entry tasks to colleagues when data were found to be incomplete. The task of 30-day follow-up proved the most onerous part of data collection. Cath-lab nursing staff were allocated this role. Conclusion: With hospital accreditation and funding models moving towards performance based quality indicators, collection of accurate and reliable information is crucial. Our experience demonstrates the successful implementation of clinical outcome registry data collection in a financially constrained public hospital environment utilising existing resources.